Insider trading and the problem of corporate agency - Thomas H. Noe (Federal Reserve Bank of Atlanta, 1995)
This paper models an economy in which managers, whose efforts affect firm performance, are able to make "inside" trades on claims whose value is also dependent on firm performance. Managers are able to trade only on "good news," that is, on returns above market expectations. Further, managers cannot trade at all unless permission for such trading is granted by shareholders. Insider trading is in derivative securities and thus does not adversely affect the firm's cost of raising funds. In this setting, it is shown that a prohibition on insider trading may still generate welfare improvement over a regime that allows shareholders to determine insider trading policy. This result obtains because insider trading, although improving managerial effort incentives for any fixed compensation level, also improves the bargaining position of shareholders relative to managers. This reduces the willingness of shareholders to provide expensive effort-assuring managerial compensation packages.
Keywords: 330; Stock market; Securities